1998
DOI: 10.1016/s0008-6363(98)00091-1
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency extracellular potentials recorded from the sinoatrial node

Abstract: Objective: To study the morphology of small extracellular potentials localized to the sinoatrial (SA) node and to elucidate its potential usefulness in evaluating SA node dysfunction. Methods: Extracellular potentials were recorded from the endocardial surface of the SA node in isolated right atrial preparations of rabbits through custom-made modified bipolar electrodes with high-gain amplification and a low-frequency (0.5-30 Hz) filter setting. Results: The potentials in and around the SA node under control c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 31 publications
6
39
0
Order By: Relevance
“…19 The present data agree with this previous work: The LPS and central regions of the SA node display small extracellular potentials that correspond with their small, slow action potentials. However, with progressive aging, the central region of the SA node shows an additional decline in the amplitude, as does the periphery region of the SA node until the whole of the SA node displays comparable electrical activity throughout.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…19 The present data agree with this previous work: The LPS and central regions of the SA node display small extracellular potentials that correspond with their small, slow action potentials. However, with progressive aging, the central region of the SA node shows an additional decline in the amplitude, as does the periphery region of the SA node until the whole of the SA node displays comparable electrical activity throughout.…”
Section: Discussionsupporting
confidence: 93%
“…However, with progressive aging, the central region of the SA node shows an additional decline in the amplitude, as does the periphery region of the SA node until the whole of the SA node displays comparable electrical activity throughout. Yamamoto et al 19 showed that blockade of the L-type calcium channel could produce such notable reductions in the amplitude of extracellular potentials. From the data presented, we believe the major contributor to the effect observed in the present data is a dramatic decline in the expression and hence recruitment of the L-type calcium channels in the aged tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of a Na ϩ channel blocker, which inactivates peripheral SAN activity but leaves firing from the central area intact, further confirmed the distinction between peripheral and central SAN. 36 Moreover, the SAN preparation used in this study is relatively easy to obtain, and the pacemaker function persists for many hours. Thus it offers considerable potential for the study of mouse models including those display abnormal pacemaker function.…”
Section: Advantages Of the Intact Mouse San Preparation For The Studymentioning
confidence: 99%
“…7 Extracellular potentials were recorded at the periphery of the sinoatrial node with the use of a pair of modified bipolar electrodes. 7 Acetylcholine (1 to 10 mol/L) or isoproterenol (0.01 to 0.1 mol/L) was added to the superfusate with cumulative increases of the concentration.…”
Section: In Vitro Electrophysiological Studymentioning
confidence: 99%